Assesment of crack arrest behaviour in modern structural steels - Taylor, Jessica (Cranfield University, 2021)
It is vital to prevent brittle cracks in large structures. This is particularly important for a number of industry sectors including offshore wind, Oil & Gas, and shipbuilding where structural failure risks loss of human life and loss of expensive assets. Wide-plate test methods allow for direct measurement of the crack arrest toughness but this kind of testing is incredibly expensive. Therefore, there is a need for cheaper and simpler test methods which are able to measure a material’s brittle crack arrest toughness. Some modern steels exhibit high Charpy energy – i.e. high initiation fracture toughness, but poor resistance to crack propagation – i.e. low crack arrest toughness. The correlation between initiation and arrest toughness measured through small-scale testing is investigated in five different steels, which include S355 structural steel (with two different thicknesses), X65 pipeline steel, two high strength reactor pressure vessel steels and EH47 shipbuilding steel. In this work, Compact Crack Arrest (CCA) testing, which is standardised in ASTM E1221, has been successfully used to measure the crack arrest toughness of thick sections of EH47 shipbuilding steel. A wide range of supplementary tests were carried out, including instrumented Charpy, drop weight Pellini, fracture toughness, tensile testing, and microscopy. Small scale mechanical tests were used to characterise the materials’ properties and the results were compared to the materials’ microstructures. The results presented in this study have been discussed in terms of the effectiveness of the CCA test method and small-scale test methods for measurement of brittle crack arrest toughness and integrity assessment of large-scale structures.
Keywords: Brittle crack arrest; ferritic steel; small-scale testing; CCA; compact crack arrest testing